Clinical characteristics and outcome of patients with autoimmune encephalitis: clues for paraneoplastic aetiology. (19th June 2020) - Iorio, R.; Damato, V.; Spagni, G.; Della Marca, G.; Vollono, C.; Masi, G.; Papi, C.; Campetella, L.; Monte, G.; Evoli, A.
Abstract : Background and purpose: Autoimmune encephalitis (AE) represents a complex syndrome with diverse clinical manifestations and therapeutic outcomes. The aim of this study was to report the clinical characteristics and the long‐term outcome of patients with paraneoplastic and idiopathic AE. Methods: All patients with subacute encephalopathy admitted to the Neurology Department of our Institution from January 2012 to May 2019 were consecutively enrolled. Patients' serum and cerebrospinal fluid were tested for neural‐specific autoantibodies by indirect immunofluorescence assays on mouse brain, rat neurons, cell‐based assays and immunoblots. Outcome was assessed by the modified Rankin Scale score. Results: From 107 adult patients with subacute encephalopathy, 50 patients were finally diagnosed with AE. Neural antibodies (Abs) were detected in 45/50 patients (90%). Leucine‐rich glioma‐inactivated protein 1 immunoglobulin G was the most frequent (6/50, 12%) Ab specific to neural surface antigens detected in adults with AE. Paraneoplastic encephalitis was diagnosed in 16/50 patients (32%). The presence of bilateral temporal lobe lesions on magnetic resonance imaging and cerebrospinal fluid restricted oligoclonal bands was associated with a higher probability to detect cancer at the time of AE diagnosis. All patients with Abs to neural surface antigens had a good outcome at last follow‐up. Severe disability at AE onset and the lack of long‐term immunosuppression predicted a poor outcome. Conclusions: Leucine‐rich glioma‐inactivated protein 1 immunoglobulin G was the most frequent Ab detected. Patients with bilateral temporal lobe lesions and oligoclonal bands have a higher probability to harbour an occult tumour. In these patients, a strict surveillance and monitoring for cancer detection is recommended.